Efek Konsumsi Konten Hiburan Digital terhadap Manajemen Stres di Komunitas Discord @motionime - Aurellia Salsabila; Fito Herlambang; Mas Siti Syakira; Steven Immanuel; Fitri Susiswani (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to investigate the effects of digital entertainment content consumption @Windah Basudara on stress management in the Motionime Discord community. This research is motivated by the need to understand how digital entertainment content consumption can contribute to stress management, especially in the context of an active digital community. A quantitative approach using a survey methodology is the research methodology employed. Primary data was collected through questionnaires distributed to 300 respondents who are members of the Motionime Discord community, who are also viewers of @Windah Basudara content. The data were analyzed using SPSS software to assess validity and reliability. The results showed that consumption of @Windah Basudara digital entertainment content has a significant positive influence on stress management. The correlation between content consumption and stress management was found to be quite strong, with a simple correlation coefficient (r) of 0.827. This suggests that participation in digital entertainment content can help reduce stress and improve mental well-being.Thus, this study recommends that stress management strategies should be paired with the use of relevant and effective digital entertainment content to improve the quality of life of digital communities.